Analysis of Language Style in Suara Bone Beradat FM Radio Broadcasts: A Descriptive Qualitative Approach - Lianingsih, Nestia; Aglia, Arla; Prabowo, Agung (International Journal of Linguistics, Communication, and Broadcasting, 2024)
This research aims to analyze and document various types of language styles used in Suara Bone Beradat FM radio broadcasts. The research method used is descriptive qualitative analysis of radio broadcast data transcription. The results of the research show that there are various types of language styles, including comparison, repetition, allusion, contradiction and emphasis. Comparative language styles include metaphor, allusion, synecdoche, and pars pro toto. Repetitive language styles include anadiplosis, mesodplosis, epizeuxis, alliteration, and epanolepsis. The language styles of satire and contradiction each consist of one data, namely innuendo and hysteron prosteron. The language style of affirmation includes parallelism and repetition. The results of this research provide a new contribution to the understanding of the use of language styles in Suara Bone Beradat FM radio broadcasts.